The Price of Perfection: Investigating the Psychological and Cultural Dimensions of Parental Pressure in Adolescent Exam-Related Stress - Zakaria, Jaffry (Journal of Educational Research and Policies, 2025)
Exam stress among high school students is a growing concern in the global educational landscape, with parental pressure emerging as a significant contributing factor. This review examines how varying parental expectations influence students’ academic stress, anxiety, and overall mental health during exam periods. While moderate parental support and involvement can positively impact motivation and academic achievement, excessive or misdirected pressure often correlates with negative outcomes, including test anxiety, emotional distress, and decreased self - esteem. By synthesizing insights from recent studies, this paper identifies key mechanisms behind these dynamics and explores the role of sociocultural factors. The discussion concludes with evidence - based recommendations for future research and interventions aimed at fostering a healthier balance between parental expectations and adolescent well - being.